2022
DOI: 10.3389/fnbeh.2022.1057736
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nonsocial and circumscribed interest images on neural mechanisms of emotion regulation in autistic adults

Abstract: IntroductionEmotion dysregulation is commonly reported among autistic individuals. Prior work investigating the neurofunctional mechanisms of emotion regulation (ER) in autistic adults has illustrated alterations in dorsolateral prefrontal cortex (dlPFC) activity, as well as concurrent atypical patterns of activation in subcortical regions related to affect during cognitive reappraisal of social images. Whereas most research examining ER in autism has focused on regulation of negative emotions, the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 115 publications
0
1
0
Order By: Relevance
“…For instance, prior studies have found higher activation in bilateral caudate when using personalized interests as a reward (in contrast to more canonical rewards such as social approval 26 or money 27 ). In addition, viewing images of a strong personal interest was associated with increased activation in the amygdala 24 , posterior cingulate 56 , and fusiform gyrus 25 in autistic children.…”
Section: Discussionmentioning
confidence: 92%
“…For instance, prior studies have found higher activation in bilateral caudate when using personalized interests as a reward (in contrast to more canonical rewards such as social approval 26 or money 27 ). In addition, viewing images of a strong personal interest was associated with increased activation in the amygdala 24 , posterior cingulate 56 , and fusiform gyrus 25 in autistic children.…”
Section: Discussionmentioning
confidence: 92%